Preclinical research and potential clinical application of traditional Chinese medicine in cancer treatment: take Astragalus and Dioscorea opposita as an example - Jia, Huizhu; Qi, Yifan; Wang, Hui; Zhang, Fengjiao; Wu, Jiarui; Zhang, Zhiqiang (Frontiers in Pharmacology, 2025)
BackgroundCancer is a complex and debilitating physical health disease that is important for social and individual health. Astragalus and Dioscorea opposita are two herbs that are traditionally used in folk medicine to treat various diseases, and they also play a role in immunizing and alleviating cancer.PurposeThis review aims to evaluate the anti-tumor potential of Astragalus and Dioscorea opposita by summarizing the active components and their known effects on tumor-related pathways, further illustrating the anti-tumor potential of traditional Chinese medicine. This study aims to explore the therapeutic effects of traditional Chinese medicines on different types of tumors.MethodsA comprehensive summary of the literature has been compiled, gathering information on the phytochemical characteristics, anti-tumor mechanisms, and the current status of both traditional Chinese and Western medicine relating to Astragalus and Dioscorea opposita. It demonstrates the previously established links between Astragalus and Dioscorea opposita and their anti-tumor properties.ResultsThe combined use of Astragalus and Dioscorea opposita enhances the immune regulatory effect through synergistic action, thereby improving the overall immune status of the body.ConclusionThis review provides a reference for experimental research in the treatment of tumors.